Pengaruh Content Marketing, Social Media Engagement, Dan Brand Image Terhadap Minat Beli Konsumen Di D’fresto Bekasi Timur - Parhusip, Yohannes Nevidelis; Fauzi, Achmad; Setyawati, Novita Wahyu (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the influence of content marketing, social media engagement, and brand image on consumer purchasing interest in D’Fresto in East Bekasi. The background of this study is based on changes in consumer behavior that increasingly rely on digital media in the purchasing decision-making process. The method used is a quantitative approach by distributing questionnaires to 119 respondents who are D’Fresto consumers. Data analysis was carried out using SmartPLS to test the relationship between variables. The results showed that content marketing had a significant effect on purchasing interest with a path coefficient value of 0.359 (p-value <0.05). Social media engagement also had a positive effect with a path coefficient of 0.209 (p-value <0.05), and brand image had a significant effect with a path coefficient of 0.351 (p-value <0.05). These findings confirm that an effective digital marketing strategy can increase consumer purchasing interest, so D’Fresto management is expected to continue to develop relevant and innovative approaches in their marketing. This study contributes to the development of digital marketing theory in the context of the local culinary industry.